1998
DOI: 10.1051/gse:19980401
|View full text |Cite
|
Sign up to set email alerts
|

Response to mass selection when an identified major gene is segregating

Abstract: -A deterministic model to predict response with mass selection when a major locus is segregating is presented. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 8 publications
(8 reference statements)
4
23
1
Order By: Relevance
“…I), followed by phenotypic selection and then standard QTL selection. The greater terminal response for phenotypic than standard QTL selection agrees with previous studies, which investigated selection on a single identified QTL [9,11,14]. The difference between phenotypic and standard QTL selection was, however, slightly less for two QTL than when their effects were concentrated into one QTL (−4.5% for two QTL compared to −6.1% for one QTL).…”
Section: Maximizing Terminal Responsesupporting
confidence: 88%
“…I), followed by phenotypic selection and then standard QTL selection. The greater terminal response for phenotypic than standard QTL selection agrees with previous studies, which investigated selection on a single identified QTL [9,11,14]. The difference between phenotypic and standard QTL selection was, however, slightly less for two QTL than when their effects were concentrated into one QTL (−4.5% for two QTL compared to −6.1% for one QTL).…”
Section: Maximizing Terminal Responsesupporting
confidence: 88%
“…The detrimental long-term effect was only avoided when the favourable allele was recessive with a large effect [12,15]. The [15]. The [2] and by Manfredi et al [13] where the purpose of the optimisation was to achieve the right emphasis given to the major gene relative to the polygenes for maximising gain without restrictions on inbreeding.…”
mentioning
confidence: 99%
“…Although in these studies the use of the available information on the major gene led to greater total genetic gain during the initial generations of selection, the accumulated response was lower when using genotype information by the time the favourable allele was fixed in both schemes (the scheme using the gene and the scheme ignoring the gene). The detrimental long-term effect was only avoided when the favourable allele was recessive with a large effect [12,15]. The [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, however, the goal is to maximize gains in current and future generations. Several studies have shown that with selection on QTL, maximization of response in the short term can result in lower cumulative responses in the longer term [10,12,19]. Methods to optimize selection on QTL to maximize a combination of short and longerterm responses have been derived [3,5,16].…”
Section: Introductionmentioning
confidence: 99%